A novel automatic 3D stitching algorithm for optical coherence tomography angiography and its application in dermatology. Issue 11 (5th August 2021) - Ji, Yubo; Zhou, Kanheng; Ibbotson, Sally Helen; Wang, Ruikang K.; Li, Chunhui; Huang, Zhihong
Abstract: Optical coherence tomography (OCT) and OCT angiography (OCTA) techniques offer numerous advantages in clinical skin applications but the field of view (FOV) of current commercial systems are relatively limited to cover the entire skin lesion. The typical method to expand the FOV is to apply wide field objective lens. However, lateral resolution is often sacrificed when scanning with these lenses. To overcome this drawback, we developed an automated 3D stitching method for creating high‐resolution skin structure and vascular volumes with large field of view, which was realized by montaging multiple adjacent OCT and OCTA volumes. The proposed stitching method is demonstrated by montaging 3 × 3 OCT and OCTA volumes (nine OCT/OCTA volumes as one data set with each volume covers 2.5 cm × 2.5 cm area) of healthy thin and thick skin from six volunteers. The proposed stitching protocol achieves high flexibility and repeatable for all the participants. Moreover, according to evaluation of structural similarity index and feature similarity index, our proposed stitched result has a superior similarity to single scanning protocol in large‐scaled. We had also verified its improved performance through assessing metrics of vessel contrast‐noise‐ratio (CNR) from 2.07 ± 0.44 (single large‐scaled scanning protocol) to 3.05 ± 0.51 (proposed 3 × 3 sub‐volume stitching method). Abstract : The proposed stitching method is demonstrated by montaging 3 × 3 OCT and OCTA volumes (nine OCT/OCTA volumes as one dataset with each volume covers 2.5 cm × 2.5 cm area) of healthy thin and thick skin from six volunteers. The proposed stitching protocol achieves high flexibility and repeatable for all the participants.